Program Eco-Pesantren Dalam Pelestarian Lingkungan - Umi Arifah; Ahmad Fauzan Hidayatullah; Anif Rizqianti Hariz (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Research has been carried out using the literature study method related to the eco-pesantren program in environmental conservation which aims to interpret the concept of eco-pesantren and educational values ​​in preserving the environment. Islam as rahmatan lil'alamin regulates human relations with the environment both through the verses of the Qur'an and as-Sunnah which are integrated in the form of regulations by the Ministry of the Environment packaged into one as the eco-pesantren program. The form of cooperation between the Ministry of Environment and the Ministry of Religion in addition to establishing the first eco-pesantren in Indonesia is the formulation of objectives, benefits, and indicators that identify the application of eco-pesantren in an educational institution. The eco-pesantren program uses the concept of environmental awareness in implementing and revitalizing it. Increased environmental awareness due to the success of socializing and supported by Islamic values ​​and spiritual life creates an ecological atmosphere both now and in the future.